Solvent induced effect on morphology and properties of disulfonated polyarylene ether sulfone block copolymer membranes for PEMFC applications. (13th February 2023) - Arnett, Natalie Y.; Devendhar Singh, Sanjay Kumar; Moxey, D'Andra; Mason, Samaiyah K.A.; Sweat, Rebekah; Plunket, Emily; Moore, Robert
Abstract: A systematic investigation to ascertain a fundamental understanding of the residual solvent effect on the bonding characteristics, thermal and mechanical properties of poly(arylene ether sulfone) (PAES) membranes was carried out. Transparent PAES membranes were synthesized using different solvents, which include dimethylformamide (DMF), dimethylacetamide (DMAc), dimethylsulfoxide (DMSO), and N -methyl-2pyrrolidone (NMP). A correlation was established between polymer-solvent interaction using Hansen solubility parameters (HSP) and Flory-Huggins interaction parameters (χP-S ). Proton conductivity, thermogravimetric analysis (TGA), dynamic mechanical analysis (DMA), and FTIR were correlated with χP-S parameter. PAES membrane derived using DMF solvent exhibited the highest proton conductivity (0.133 ± 0.01 S∙cm −1 ). Scanning electron microscopy (SEM) confirmed the formation of defect-free membranes. The presence of residual solvent in the membranes resulted in a plasticizer effect which was confirmed through storage modulus behavior from DMA. This study will act as a standard protocol for the development of high-performance PAES membranes with desired properties for polymer fuel cells applications. Graphical abstract: Image 1 Highlights: Effect of residual solvent on transparent PAES membrane was carried out. HSP and χP-S parameters was used to establish a correlation between PAES-solvent. Proton conductivity, thermogravimetric analysis (TGA), DMA, and FTIR were correlated with χP-S interaction parameter. PAES-DMF membrane exhibited the highest proton conductivity (0.133 ± 0.01 S∙cm −1 ). Plasticizer effect due to residual solvent was confirmed through DMA.